Endothall behavior in five aquatic weeds - Ortiz, Mirella F., author; Nissen, Scott, advisor; Gray, Cody, advisor; Dayan, Franck, committee member; Meiman, Paul, committee member (Colorado State University. Libraries, 2018)
Endothall is one of the original aquatic herbicides being primarily to control submersed plants since 1960. Endothall is considered a contact herbicide, in a chemical class of its own, it is a serine/threonine protein phosphatase inhibitor, which has broad-spectrum control and is effective in controlling both monocotyledons and dicotyledons. Eurasian watermilfoil (Myriophyllum spicatum L.) (EWM), hydrilla [Hydrilla verticillata (L.f.) Royle], curlyleaf pondweed (Potamogeton crispus L.) (CLP), and sago pondweed (Potamogeton pectinatus L.) (SPW) are submersed aquatic species considered troublesome throughout the United States, which can be controlled with endothall. These species can form extensive, undesirable surface canopies, which can negatively impact water flow, water quality, economic and ecological value of water bodies. Although endothall is considered a contact herbicide, many field observations suggest that it might have systemic activity. The goals of this research were to (1) determine maximum herbicide absorption and absorption rate, (2) evaluate herbicide translocation from shoots to roots in EWM, two hydrilla biotypes, CLP, and SPW, and (3) evaluate herbicide desorption in EWM and two hydrilla biotypes. Each weed species was clonally propagated from apical shoot cutting or turions/tubers when present. For herbicide absorption and translocation, plants of each species with developed roots and 15 cm of shoot growth were transferred to test tubes containing unwashed silica sand and sealed at the top with a low melting point eicosane wax to isolate the root system from the water column. Plants were exposed to the herbicide over 192 h. At predetermined time points three plants of each species were harvested, divided into shoot and root tissue, and oxidized. Herbicide desorption was evaluated over 96 h. Endothall absorption was linear in hydrilla, while in EWM, CLP and SPW it best fit an asymptotic rise function. Translocation to EWM, CLP, and SPW roots was limited, reaching a maximum translocation of 8%, 3% and 1% of total absorbed radioactivity, respectively. Monoecious and dioecious hydrilla showed a linear increase without reaching maximum absorption or translocation 192 HAT. Endothall translocation to monoecious and dioecious hydrilla roots was 18% and 16% of total absorbed radioactivity, respectively. Herbicide desorption was less than 30% for all the three species evaluated. These data provide strong evidence that endothall behaves as a systemic herbicide in these aquatic species.